Micro-Grids - Applications, Operation, Control and Protection 2019
DOI: 10.5772/intechopen.86431
|View full text |Cite
|
Sign up to set email alerts
|

Microgrid Protection Systems

Abstract: Micro grids are miniature version of conventional large power grids functioning either autonomously or with inter connection to the main grid. Primary function of micro grid is to serve power at distribution level. Distributed energy resources (DERs) connected to the micro grid enables reliable and efficient operation of micro grid. Protection of micro grids assumed importance due to increased penetration of distributed energy resources. Most of the distribution systems in earlier days are radial in nature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In contrast, ring network structures allow for power to flow in both directions, allowing the load to obtain power from two separate sources if one feeder fails. This ensures that the load, or a portion of it, is still supplied with power [30]. Due to the constant running of industrial processes, distribution networks in these locations frequently use ring networks, which can result in significant financial losses in the event of a system outage.…”
Section: Protection Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, ring network structures allow for power to flow in both directions, allowing the load to obtain power from two separate sources if one feeder fails. This ensures that the load, or a portion of it, is still supplied with power [30]. Due to the constant running of industrial processes, distribution networks in these locations frequently use ring networks, which can result in significant financial losses in the event of a system outage.…”
Section: Protection Coordinationmentioning
confidence: 99%
“…The ring opens at one end, typically at one of the sources. Another approach is to use differential protection for the portion connecting the sources, but selectivity cannot be achieved for every configuration [30,31].…”
Section: Protection Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature review found that the problem of high demand for energy production is the main problem. Behind this concept, many scholars try to study the new paradigm of looking for energy autonomy in several countries in response to this problem; in [13,14] the authors studied the problem regarding the local energy organization management in the European Union and proposed autonomous energy regional organizations. Furthermore, the study proposed the solution to the preparation and implementation of the grid services as a part of the local public autonomous energy system [15].…”
Section: Autonomous Energy Managementmentioning
confidence: 99%
“…Microgrids are alternatively called energy management systems that are operated in coordination to reliably supply electricity to a cluster of loads and distribute generated units. Furthermore, they are energy storage systems connected to the host power system at the distribution level at a single point of connection, or PCC [13] Microgrids can also be totally self-contained and independent of the grid (off-grid).…”
Section: Introductionmentioning
confidence: 99%